Teachers’ self-efficacy in the implementation of inclusive education: Literature review - ika febrian kristiana (Universitas Ahmad Dahlan, 2018)
Self-efficacy of teachers is a teacher's belief in self-competence that can be demonstrated in a given situation. Self-efficacy teachers have been extensively researched including in the context of inclusive education involving students with special needs. This study aims to conduct a literature review of the predictors and consequences of teacher self-efficacy in the setting of inclusive education involving S. Search literature using online database include ERIC, ProQuest, and Science Direct. The keywords used in the search was (